Eupafolin Suppresses Esophagus Cancer Growth by Targeting T-LAK Cell-Originated Protein Kinase - Fan, Xiaoming; Tao, Junyan; Cai, Xin; Fredimoses, Mangaladoss; Wu, Junzi; Jiang, Zhihui; Zhang, Kunpeng; Li, Shude (Frontiers in Pharmacology, 2019)
Abstract Eupafolin is the main bioactive component extracted from the traditional Chinese medicine Ay Tsao (Artemisia vulgaris L.), and its anti-tumor activity have had been studied in previous researches. T-LAK cell-originated protein kinase (TOPK) belongs to serine/threonine protein kinase, is highly expressed in several cancer cells and tissues, such as colon cancer, lung cancer, esophagus cancer and so on. Therefore, it was recognized as an important target for treating tumors. Nowadays, we found that Eupafolin suppressed TOPK activities at the first time in vitro and in vivo. The cells study indicated that Eupafolin suppressed TOPK activities in JB6 Cl41 and KYSE450 cells. Furthermore, knockdown of TOPK in KYSE450 cells decreased their sensitivities to Eupafolin. The animal study showed that the injection of Eupafolin in patient-derived xenograft (PDX) mouse effectively suppressed tumor growth. Histone H3 and Ki67 were reduced and cleaved caspase 3 was increased in tumor tissues after Eupafolin treatment. To sum up, Eupafolin as an TOPK inhibitor can suppress growth of esophagus cancer in vitro and in vivo. The TOPK downstream signaling molecule Histone H3 in tumor tissues was also reduced after Eupafolin treatment. In short, Eupafolin can suppress growth of esophagus cancer cells as an TOPK inhibitor both in vitro and in vivo.